Distance Between the Most Prominent Labial Surface of Maxillary Central Incisors to the Posterior Limit of Incisive Papilla in Various Arch Forms - Khanal, Anuj; Parajuli, P; Niraula, SR; Singh, RK; Suwal, P (Journal of Nepalese Prosthodontic Society, 2019)
Introduction: Arranging artificial teeth has always been a challenging work since edentulous alveolar ridges are in a constant verge of physiological resorptive changes. Incisive papilla is a reliable biometric guide which can be used as a reference for arrangement of anterior teeth, since it is a stable intraoral anatomical landmark unless surgically modified.Objective: This study was conducted to determine the mean distance between the most prominent labial surface of maxillary central incisors to the posterior limit of incisive papilla in various arch forms.Materials and Methods: The study was carried out among 170 undergraduate students of BPKIHS, after obtaining ethical clearance from Institutional Review Committee, BPKIHS. Maxillary impressions were made with alginate impression materials and casts were poured with dental stone. Distance from the posterior limit of incisive papilla to maximum convexity of central incisor (Papillo-Incisal Distance, PID) was measured with a Digital Vernier caliper with a precision of 0.01mm. The arch forms were analyzed and classified into ovoid, tapering and squarish arch, subjectively based on morphological parameters. The intra-examiner reliability of the measurement was tested in 17 casts calculating Cronbach’s Alpha. Pearson Chi-square test was applied to explore the relation of the arch forms with age and gender. One-way ANOVA was used to check the association between the mean PID between with different arch forms.(p value = 0.05)Results: The mean distance from the labial surface of maxillary central incisors to the posterior limit of incisive papilla was 11.58±1.32 mm. The mean papillo-incisal distance varied with respect to different arch forms which was statistically significant (P